2021
DOI: 10.3389/fonc.2021.660273
|View full text |Cite
|
Sign up to set email alerts
|

A Poliovirus Receptor (CD155)-Related Risk Signature Predicts the Prognosis of Bladder Cancer

Abstract: BackgroundBladder cancer is an aggressive and heterogeneous disease associated with high morbidity and mortality. And poliovirus receptor (PVR or CD155) played crucial roles in tumor immune microenvironment and cancer development. However, their association remains obscure.MethodsA total of 797 patients from TCGA and GEO databases were employed in our study, in which 285 cases were set as the training cohort and 512 were defined as the validation cohort. Our own Xiangya cohort with 57 samples was also used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…An effective biomarker to predict ICB immunotherapy response is important for precise treatment. However, although CD8 + T effector signatures, hypoxia-related genes, and PVR-related genes have been shown to predict BLCA immunotherapy [40][41][42], these indicators often involve more genes and are difficult to measure. GNG4 as a single gene may have the advantage compared with these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…An effective biomarker to predict ICB immunotherapy response is important for precise treatment. However, although CD8 + T effector signatures, hypoxia-related genes, and PVR-related genes have been shown to predict BLCA immunotherapy [40][41][42], these indicators often involve more genes and are difficult to measure. GNG4 as a single gene may have the advantage compared with these biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…CD155 is rarely expressed in most normal tissues, but is overexpressed in various carcinomas [7][8][9][10][11][12]. In terms of BC, Cong et al [18] analyzed 797 patients from The Cancer Genome Atlas and Genome Expression Omnibus to establish a relationship between the mRNA expression of CD155 and the prognosis of several cancer types including BC. Zhang et al [19] investigated 228 BC patients who underwent RC and reported that CD155 protein was significantly overexpressed on the membrane of tumor cells compared to matched normal urothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in addition to being expressed in virusinfected cells (43), these ligands are overexpressed in several hematological and solid tumors (5, 50-52). Noticeably, these ligands, in particular PVR, are potential prognostic markers in AML (53,54), MM (55), hepatocellular carcinoma (56), and bladder urothelial carcinoma (BLCA) (57). As we have previously reported, PVR expression is directly under the control of p53 at promoter level (47), whilst the transcriptional regulation of Nectin-2 remains more widely to be explored (58).…”
Section: Pvr and Nectin-2 In Cancer Patientsmentioning
confidence: 97%